Microglial derived extracellular vesicles activate autophagy and mediate multi‐target signaling to maintain cellular homeostasis. Issue 1 (25th November 2020) - Van den Broek, Bram; Pintelon, Isabel; Hamad, Ibrahim; Kessels, Sofie; Haidar, Mansour; Hellings, Niels; Hendriks, Jerome J.A.; Kleinewietfeld, Markus; Brône, Bert; Timmerman, Vincent; Timmermans, Jean‐Pierre; Somers, Veerle; et al.
Abstract: Microglia, the immunocompetent cells of the central nervous system (CNS), play an important role in maintaining cellular homeostasis in the CNS. These cells secrete immunomodulatory factors including nanovesicles and participate in the removal of cellular debris by phagocytosis or autophagy. Accumulating evidence indicates that specifically the cellular exchange of small extracellular vesicles (EVs), participates in physiology and disease through intercellular communication. However, the contribution of microglial‐derived extracellular vesicles (M‐EVs) to the maintenance of microglia homeostasis and how M‐EVs could influence the phenotype and gene function of other microglia subtypes is unclear. In addition, knowledge of canonical signalling pathways of inflammation and immunity gene expression patterns in human microglia exposed to M‐EVs is limited. Here, we analysed the effects of M‐EVs produced in vitro by either tumour necrosis factor alpha (TNFα) activated or non‐activated microglia BV2 cells. We showed that M‐EVs are internalized by both mouse and human C20 microglia cells and that the uptake of M‐EVs in microglia induced autophagic vesicles at various stages of degradation including autophagosomes and autolysosomes. Consistently, stimulation of microglia with M‐EVs increased the protein expression of the autophagy marker, microtubule‐associated proteins 1A/1B light chain 3B isoform II (LC3B‐II), and promoted autophagic flux in live cells. To elucidate the biological activities occurring at the transcriptional level in C20 microglia stimulated with M‐EVs, the gene expression profiles, potential upstream regulators, and enrichment pathways were characterized using targeted RNA sequencing. Inflammation and immunity transcriptome gene panel sequencing of both activated and normal microglia stimulated with M‐EVs showed involvement of several canonical pathways and reduced expression of key genes involved in neuroinflammation, inflammasome and apoptosis signalling pathways compared to control cells. In this study, we provide the perspective that a beneficial activity of in vitro cell culture produced EVs could be the modulation of autophagy during cellular stress. Therefore, we use a monoculture system to study microglia‐microglia crosstalk which is important in the prevention and propagation of inflammation in the brain. We demonstrate that in vitro produced microglial EVs are able to influence multiple biological pathways and promote activation of autophagy in order to maintain microglia survival and homeostasis.